ANALISIS POTENSI KECELAKAAN AKIBAT KERJA DENGANPROSEDUR HAZARD IDENTIFICATION, RISK ASSESMENT,AND DETERMAINING CONTROL (HIRADC)DI PT ANEKA ADHILOGAM KARYA - Candra, Lian; , Tarwaka, PGDip., Sc., M.Erg (2016)
PT. Aneka AdhilogamKaryawas one of the metal foundry company in Batur, Ceper, Klaten. The production activities encompassed theprocess of induction, casting, machining and finishing. The workplace had a high risk that caused accidents. The needed things to be implemented were Hazard Identification, Risk Assessment and Determining Control. This study aims at analyzing the potential for Occupational accidents with the HIRADC procedure. The type of this research was an observational descriptive research with aExhausted Sampling of 64 samples obtained by using Exhausted Sampling. The result of this research showed that there were 42 potential sources of danger with which 16 sources of danger included in the veryhigh level of risk, 15 sources of danger included in the high level of risk, 9 sources of danger included in the moderate level of risk and the other second sources of danger included in a low level of risk. It can be concluded that the source of potential danger came from unsafe working environment, uncomfortable working attitude and equipment or machinery which was not safe. Therefore, there are still other many potential sources of danger included in the veryhigh and high level of risk in the company. Companies need to make priorities and risk control in accordance with the hierarchy of risk control.